2021
DOI: 10.1039/d0me00173b
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating and decontaminating of sarin by heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin: MD simulations and QM calculations

Abstract: Chemical warfare agents (CWAs) such as sarin are still available and their toxicity is a real danger. This study aims at investigating the ability of heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin (M-β-CD) to trap and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Notably, the b-CD molecule containing seven glucopyranose units has desirable features, such as cavity diameter and volume that allow for inclusion of many types of drugs (B6.0-6.5 Å; and B262 Å 3 , respectively) and relatively low cost of production owing to advances in synthetic technology. 11 In the past decade, extensive research on b-CDs and b-CD-drug complexes has been conducted via computer simulations [12][13][14][15][16][17][18] and experiments 14,[18][19][20][21][22][23][24][25] with the goal of developing new DDSs. For instance, a recent experimental study on the inclusion complex of Sulfobutyl-b-CD and Celastrol demonstrated that the formation of the inclusion complex enhances Celastrols intestinal permeability and stability under physiological and biological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the b-CD molecule containing seven glucopyranose units has desirable features, such as cavity diameter and volume that allow for inclusion of many types of drugs (B6.0-6.5 Å; and B262 Å 3 , respectively) and relatively low cost of production owing to advances in synthetic technology. 11 In the past decade, extensive research on b-CDs and b-CD-drug complexes has been conducted via computer simulations [12][13][14][15][16][17][18] and experiments 14,[18][19][20][21][22][23][24][25] with the goal of developing new DDSs. For instance, a recent experimental study on the inclusion complex of Sulfobutyl-b-CD and Celastrol demonstrated that the formation of the inclusion complex enhances Celastrols intestinal permeability and stability under physiological and biological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recently, there has been a surge in pure theoretical studies that have provided new insights into the binding mode and interaction mechanism of host-guest systems. [5][6][7][8][9][10][11][12][13][14][15][16] b-Cyclodextrin (b-CD) is one of the most common and significant host molecules and is internally hydrophobic and externally hydrophilic, and is often used to encapsulate guest molecules containing a phenyl group. Due to its flexible nature and asymmetric shape, the conformational space of b-CD inclusion complexes is rather complicated.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 Recently, there has been a surge in pure theoretical studies that have provided new insights into the binding mode and interaction mechanism of host–guest systems. 5–16…”
Section: Introductionmentioning
confidence: 99%